The ‘Male Flower’ of Ricinus communis (Euphorbiaceae) Interpreted as a Multi-Flowered Unit - Claßen-Bockhoff, Regine; Frankenhäuser, Hebert (Frontiers in Cell and Developmental Biology, 2020)
One of the most exciting questions in botany refers to the nature of the angiosperm flower. While most flowering structures are easily identified as flowers, there are few examples lying in-between flowers and inflorescences. Such an example is the staminate unit in Ricinus communis (Euphorbiaceae) famous for its branched `staminal trees´. The units were controversially interpreted in the past. Today, they are seen as flowers with multiple branched stamen-fascicles questioning the flower-inflorescence boundary. In the present paper, the recently described floral unit meristem is used to interpret the staminate units in Ricinus. This meristem shares almost all characteristics with a flower meristem, but differs from it in the number of fractionation steps resulting in many-flowered units. Reinvestigation of the development confirms previous studies illustrating up to six fractionation steps before the meristem merges into anther-formation. Fractionation starts early at a naked meristem, covers simultaneously its whole surface, shows an all-side instead of unidirectional splitting pattern and continues repeatedly. Based on the present knowledge, it is plausible to interpret the staminate unit as a floral unit with multiple staminate flowers each reduced to a single anther. This interpretation is in accordance with the many examples of reduced flowers in the Euphorbiaceae.